2004
DOI: 10.1111/j.1524-4733.2004.74006.x
|View full text |Cite
|
Sign up to set email alerts
|

Costs and Benefits of Influenza Vaccination and Work Productivity in a Colombian Company from the Employer's Perspective

Abstract: Among the studied volunteers, ILI has significant impact on work productivity in terms of indirect costs. Implementing an influenza vaccination program would reduce the burden of ILI and save substantial amounts of money for the company.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 17 publications
(34 reference statements)
1
46
1
Order By: Relevance
“…Rates between less than 15% for systemic reactions (including fever, myalgia, etc) and up to 65% for local reactions (acute inflammation at the point of injection) have been reported 5,11,23,29) . In the present study, the rate of adverse events reported following VAXIGRIP ® was 32.74%, well within the published range.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rates between less than 15% for systemic reactions (including fever, myalgia, etc) and up to 65% for local reactions (acute inflammation at the point of injection) have been reported 5,11,23,29) . In the present study, the rate of adverse events reported following VAXIGRIP ® was 32.74%, well within the published range.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for these differences are unclear and are probably specific to this particular company. For example, in the recently published study by Morales et al on a workplace vaccination campaign against influenza in a Columbian bank 11) , the bank operated a policy of non-replacement for sick leave of less than 20 d duration. In this case, including operating income in cost-savings calculations increased savings 10 to 15 times.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another Brazilian study of the benefits of influenza vaccination, involving a study of commercial aircrew, found a reduction of 39.5% in episodes of influenza-like illness and a 26% reduction in working days lost (Mixeu et al, 2002). Another evaluation of influenza vaccination in Colombia suggested savings of $6.4-25.8 on labour costs and these saving increased to $ 89.3-237.8 when operating income was factored in (Morales et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies regarding the use of vaccination in private companies have mainly focussed on influenza vaccines and have shown that vaccination can reduce the disease burden for the employer in a variety of countries and industries (Beran & Moravik, 2003;Bridges et al, 2000;Burckel et al, 1999;Campbell & Rumley, 1997;Kawabayashi et al, 2013;Lee et al, 2010;Leighton et al, 1996;Liu et al, 2004;Lugovskaia et al, 2014;Mixeu et al, 2002;Morales et al, 2004;Olsen et al, 1998;Samad et al, 2006).…”
Section: Introductionmentioning
confidence: 99%